The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.18488/journal.73.2020.81.123.132
|View full text |Cite
|
Sign up to set email alerts
|

Accountability through Integrated Reporting: The Awareness and Challenges in Malaysia

Abstract: The objectives of this paper are twofold: the first objective is to critically analyze the literature of integrated reporting in clarifying the role and form of integrated reporting; and the second objective is to survey on the awareness of Malaysian accountants about integrated reporting. with the sustainability process (Brown, de Jong, & Levy, 2009; Buhr, Gray, & Milne, 2014). However, recent development shows that readers are overloaded with the increased complexity and lengthy information, thereby

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…The International Integrated Reporting Framework has been attempting to unify integrated reporting policy across national boundaries through IIRC efforts, thus ensuring comparability and consistency in reporting business activities within and across countries. Integrated reporting enables businesses to keep up with international developments by focusing on true value drivers (Mohammed et al , 2020), facilitating access to international markets. However, the increasingly sophisticated nature of business transactions can be difficult to understand, particularly with respect to the growing number of business organizations that cross international boundaries (Eccles and Krzus, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The International Integrated Reporting Framework has been attempting to unify integrated reporting policy across national boundaries through IIRC efforts, thus ensuring comparability and consistency in reporting business activities within and across countries. Integrated reporting enables businesses to keep up with international developments by focusing on true value drivers (Mohammed et al , 2020), facilitating access to international markets. However, the increasingly sophisticated nature of business transactions can be difficult to understand, particularly with respect to the growing number of business organizations that cross international boundaries (Eccles and Krzus, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The accounting literature offers differing views of integrated reporting schemes that have been separately used when interpreting corporate reporting phenomena (see e.g. Humphrey et al , 2017; Jensen and Berg, 2012; Idowu et al , 2016; Mohammed et al , 2020). However, the literature largely appreciates the use of a multidimensional theoretical perspective to interpret complex multifaceted phenomena such as integrated reporting (Cormier et al , 2005; Dragomir and Dumitru, 2023; Herold et al , 2019; Jayasiri et al , 2023).…”
Section: Institutional and Stakeholder Interaction In The Context Of ...mentioning
confidence: 99%
See 1 more Smart Citation
“…IR has received acceptance in Malaysia through the involvement of key stakeholders in corporate reporting in the country. Organisations that have demonstrated keen enthusiasm for IR include the Malaysian Institute of Accountants (MIA), Securities Commission Malaysia (SCM), and the Malaysia Association of Certified Public Accountants (MACPA) (Mohammed et al, 2020). The MIA, one year after the IIRC released the first IR framework in 2013, formed the Integrated Reporting Steering Committee (IRSC) to actively promote the roll-out of IR in Malaysia.…”
Section: Ir In Malaysiamentioning
confidence: 99%
“…Adhariani and de Villiers's (2018) findings on perceived advantages were consistent with the MIA-ACCA (2016) survey on Malaysia, which showed that the benefits of IR included fostering integrated thinking, enhancing communication with external stakeholders, and enhancing transparency and governance. Hence, better decision making by focusing on the actual value drivers of business (Mohammed et al, 2020).…”
Section: Benefits Of Integrated Reportingmentioning
confidence: 99%